Comparative transcriptomic analysis of tumor- infiltrating canine natural killer cells and candidate biomarkers from first-in-dog NK immunotherapy trials - Razmara, Aryana M.; Lammers, Marshall; Judge, Sean J.; Sholevar, Cyrus J.; Murphy, William J.; Gaskill, Cameron E.; Culp, William T. N.; Gingrich, Alicia A.; Morris, Zachary S.; Rebhun, Robert B.; Brown, C. Titus; Vail, David M.; et al. (Frontiers in Immunology, 2025)
IntroductionNatural killer (NK) cells have great potential to extend the promise of cancer immunotherapy, but additional research is needed to improve their efficacy in solid cancers. Dogs develop spontaneous cancers with striking similarities to humans and can serve as a crucial link to bridge murine studies and human clinical trials to improve treatment outcomes across species and identify potential biomarkers of response.MethodsUsing single-cell RNA sequencing (scRNAseq), we integrated blood, tissue, and tumor samples from dog and human donors to compare NK cell gene expression and develop a canine sarcoma infiltrating NK signature. Canine tissue and tumor NK cell signatures were then used to contextualize NK cell changes in first-in-dog immunotherapy clinical trials.ResultsTumor infiltrating NK cells from both canine and human sarcomas exhibited enhanced migration with a simultaneously exhausted signature that most closely correlated transcriptionally with NK cells isolated from the liver. We also analyzed peripheral blood NK cells from dogs on first-in-dog clinical trials undergoing three distinct NK-targeting immunotherapy regimens, observing that dogs with favorable responses demonstrated increased NK proportions posttreatment. Genes upregulated in NK cells in the peripheral blood of good responders included genes associated with activated NK cells and revealed post-treatment gene expression changes in the blood as a predictor of response.DiscussionOverall, NK effector functions are well adapted to their tissue of residence but dysregulated in sarcoma infiltrating NK cells despite enhanced migration. We describe NK cell trends across canine clinical trials as a platform through which we can elucidate mechanisms of response and determine novel immunotherapy strategies to improve cancer outcomes in both humans and dogs.